CAR T-cell therapy in autoimmune diseases: a promising frontier on the horizon - Wu, Dehong; Xu-Monette, Zijun Y.; Zhou, Jia; Yang, Kepeng; Wang, Xinchang; Fan, Yongsheng; Young, Ken H. (Frontiers in Immunology, 2025)
Although current treatments for autoimmune diseases can effectively control symptoms, they rarely lead to cures and often require lifelong use, accompanied by considerable adverse effects. This emphasizes the urgent need for more targeted therapies that offer long-term efficacy and curative potential. Chimeric antigen receptor (CAR) T-cell therapy presents a promising option by specifically targeting and eliminating autoreactive B cells, with the potential to reset the patient’s immune system and promote long-term immune balance. Originally developed for treating hematologic malignancies, where it has achieved remarkable success, recent studies have demonstrated substantial promise of CAR T-cell therapy, such as systemic lupus erythematosus (SLE) and myasthenia gravis. This article provides an overview of the current progress in CAR T-cell therapy for autoimmune diseases, focusing on five key approaches: CD19-targeted CAR T cells, CAR T cells targeting long-lived plasma cells, CAR T cells targeting specific autoantibodies, organ-specific CAR regulatory T cells (Treg cells), and mRNA-engineered CAR T cells. Additionally, this article discusses strategies for optimizing CAR T-cell therapy, including “off-the-shelf” allogeneic CAR T-cell therapy, combined CAR T-cell therapy, establishing timely consensus guidelines for their application in autoimmune diseases, and risk stratification strategies aimed at enhancing the personalization of treatments and minimizing adverse effects. While current research results are promising, further large-scale clinical trials and long-term follow-up are essential to thoroughly evaluate the safety and efficacy of CAR T-cell therapy in autoimmune diseases.